STRATEGI KOMITE SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN DI SD NEGERI 1 LHOKNGA - Sri Wardiah; Murniati .; Djailani . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2015)
Abstract: The strategy of school committee is one factor of the success of educational program that includes the knowledge and motivation in improving the education quality. This study aimed to find out what the program of school committee, the strategy/approach used by the school committee, and the obstacle faced by the school committee in improving the education quality. This study used qualitative approach with descriptive method. Techniques of data collection used were observation, interview, and documentation study. Subjects of this study were chairperson of school committee, principal, and teachers. The results of the study showed that: (1) the programs of school committee in improving the education quality included regular meeting of school committee for each semester, participating to approve the School Activity and Budget Plans (RKAS)/School Budget (RAPBS), giving suggestion and recommendation to local government to improve the quality of educational services based on the school’s need. However, the implementation of these programs was not effective yet. (2) The strategies of school committee in improving the education quality were regular meeting with school community at the end of each semester, together with the school, formulating vision and mission of school, formulating RKAS and RAPBS, and developing the potential to better prospect. (3) The obstacle faced by school committee in improving the education quality was the lack of communication between school and school committee because of the lack of time had by school committee, so that the programs of school committee became less effective.Keywords: Strategy, Education Quality, and School CommitteeAbstrak: Strategi komite sekolah merupakan salah satu faktor keberhasilan program pendidikan yang meliputi pengetahuan dan motivasi dalam peningkatan mutu pendidikan. Tujuan penelitian ini untuk mengetahui bagaimana program komite sekolah, strategi/pendekatan komite sekolah dan kendala komite sekolah dalam peningkatan mutu pendidikan. Pendekatan yang digunakan dalam penelitian ini yaitu pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data dilakukan dengan pedoman observasi, pedoman wawancara, dan studi dokumentasi. Subjek dalam penelitian ini adalah komite sekolah, kepala sekolah dan guru. Hasil penelitian menunjukkan bahwa: (1) Program komite sekolah dalam peningkatan mutu pendidikan meliputi: rapat rutin komite sekolah setiap semester, ikut mensahkan RKAS/RAPBS, Menyampaikan usulan dan rekomendasi kepada pemerintah daerah untuk meningkatkan kualitas pelayanan pendidikan sesuai dengan kebutuhan sekolah, namun dalam pelaksanaannya belum efektif (2) Strategi komite sekolah dalam peningkatan mutu pendidikan melalui kegiatan diantaranya: Rapat rutin dengan warga sekolah pada setiap akhir semester, Bersama-sama sekolah membuat rumusan visi dan misi sekolah, menyusun RKAS dan RAPBS serta mengembangkan potensi kearah yang lebih baik, (3) Kendala komite sekolah dalam peningkatan mutu pendidikan adalah kurangnya komunikasi antara sekolah dengan komite sekolah karena kurangnya waktu yang dimiliki oleh komite sekolah, sehingga program komite sekolah menjadi kurang efektif.Kata Kunci: Strategi, Mutu Pendidikan, dan Komite Sekolah